PENGARUH KUALITAS PELAYANAN DAN KETEPATAN WAKTU PENGIRIMAN TERHADAP KEPUASAN KONSUMEN : Survey Pada Konsumen PT. Pos Indonesia (Persero) Kantor Pos Cabang Indihiang - Akbar Maula Fachreza; Ari Arisman; Barin Barlian (Melati Institute, 2022)
This study aims to determine the effect of service quality and timeliness of delivery on consumer satisfaction (survey on consumer of PT Pos Indonesia (Persero) Indihiang). The results showed that there was a positive and significant effect of service quality on consumer satisfaction at PT POS Indonesia (Persero) branch post office Indihiang. The results showed that there was a positive influence and timeliness of delivery on consumer satisfaction at PT POS Indonesia (Persero) branch post office Indihiang. Based on this, it can be concluded that if there is an increase in the value of service quality, the value of consumer satisfaction will also increase. Based on this, it can be concluded that if there is an increase in the value of on time delivery, the value of consumer satisfaction will also increase.